(untitled) (Research, Society and Development, 2022)
Montrichardia linifera is an aquatic macrophyte widely used by the population, presenting antibacterial, antioxidant, antiplasmodic, insecticidal and antimalarial activities. This study aimed to evaluate the phytochemical composition and biological activities of extracts obtained from M. linifera leaves collected in different locations. Hexanic (HXE), hydroalcoholic (HAE) and methanolic (ME) extracts were prepared from leaves from four collection points in the state of Piauí, Brazil: Porto dos Tatus (PT), Lagoa do Bebedouro (LB), Galego (G) and Morros da Mariana (MM). Qualitative and quantitative phytochemical assays, evaluation of in vitro cytotoxicity against three tumor cell lines (HL-60, HCT-116 and B16-F10), evaluation of antibacterial activity against Escherichia coli and Staphylococcus aureus and analysis of antioxidant potential by DPPH were carried out and ABTS. The extracts showed the presence of alkaloids, organic acids, flavonoids, phenols and tannins, with their presence varying according to the place of collection. The HXE-G sample had the highest percentage of flavonoids. The ME-G and HAE-G samples had the highest levels of phenolic compounds. The HXE-G, HAE-G and ME-G extracts showed a high percentage of inhibition against the three tumor strains tested. HXE-MM had a bacteriostatic effect against both strains of bacteria tested. The samples that showed better antioxidant activity were ME-G and HAE-G. These results demonstrate that the plant has a phytochemical variability, depending on the geographic location and the type of solvent used in the extraction process. Thus, the extracts obtained from M. linifera leaves present a variety of secondary metabolites with potential biological activity.